Low risk quantifiers: a game-theoretical approximation to the dp-restriction on IV2-presentationals - Gärtner, Hans-Martin (Proceedings of the Amsterdam Colloquium, 2007)
Low risk quantifiers (LRQs) are quantifiers for which an opponent has no superior falsification strategy in a GTS-style verification game. LRQs are shown to closely approximate the class of DP-quantifiers allowed in a presentational construction of German involving prosodically and information-structurally integrated V2 clauses. The notion of "risk" will be linked to a speaker strategy in competitive argumentation.